Molecular characterization and lineage analysis of canine astrovirus strains from dogs with gastrointestinal disease in Ecuador based on ORF-2 gene analysis - Loor-Giler, Anthony; Santander-Parra, Silvana; Castillo-Reyes, Sara; Campos, Martín; Mena-Perez, Renan; Prado-Chiriboga, Santiago; Nunez, Luis (Frontiers in Veterinary Science, 2025)
Canine Astrovirus (CaAstV) part of the Astroviridae family and genus Mamastrovirus, is a linear RNA virus with a genome of approximately 6.6 kb with three open reading frames (ORF): ORF1a and ORF1b, which code for the most conserved non-structural proteins, and ORF2, which code for the capsid protein, the most variable region of the genome. This pathogen has been linked to gastrointestinal infections, primarily causing symptoms such as vomiting, diarrhea, lethargy and severe dehydration, mainly in co-infection with other enteric viruses. In the present study, the presence of CaAstV was identified in dogs with gastrointestinal disease in Ecuador using RT-qPCR with hydrolysis probes, these samples have also tested positive for canine parvovirus type 2 (CPV-2) and canine coronavirus (CCoV). Positive samples were used for end-point RT-PCR amplification and sequencing of ORF-2 using Sanger technology. The sequences were subjected to phylogenetic analysis to determine lineages and possible recombination events. Of the 502 samples tested, 336 were found to be positive for CaAstV, 49.4% in co-infection with CPV-2, 1% in co-infection with CCoV, and 4% in simultaneous infection with all three viruses. The presence of 4 of the 5 previously reported CaAstV lineages were identified, and three possible recombinant strains were identified. Given the high frequency of CaAstV infections in dogs with gastroenteritis and its high genetic variability, it emphasizes the need to implement routine diagnostic measures that include this pathogen as one of the main causes of the disease and a risk agent in case of multiple infections.